Level of Partograph completion and healthcare workers' perspectives on its use in Mulago National Referral and teaching hospital, Kampala, Uganda - John Mukisa; Isha Grant; Jonathan Magala; Andrew S. Ssemata; Patrick Z. Lumala; Josaphat Byamugisha (BMC, 2019)
Abstract Background The appropriate use of the Partograph allows early identification of labour related complications and prevents deaths. We, therefore, sought to determine the level of Partograph completion and healthcare worker perspectives towards its utilization. Methods This study had two components; a hospital-based cross-sectional descriptive chart review at the Mulago National Referral Hospital, Kampala, Uganda and a qualitative study involving four Focus Group Discussions (FGDs) with ward nurses, midwives and postgraduate residents. Data from the FGDs were analyzed using thematic -content analysis in Open Code software. The quantitative data were summarized using descriptive statistical analysis, means and proportions. Results Among the 355 Partographs reviewed, 79.1% had incomplete documentation of age, 52.7% gravidity, and 3.2% parity. In about 61%, the specific parameters for fetal monitoring, maternal monitoring and labour progress were incomplete. From the FGDs, the healthcare workers reported being unable to complete the Partographs due to the overwhelming numbers of expectant mothers and other staff responsibilities. Congestion in the maternity ward reduced the Partograph completion rates. The availability of other monitoring tools, limitation in skills, inadequate equipment and supplies, and the state of the mother at the presentation to the hospital all made Partograph use and completion challenging. Conclusions The majority of Partographs started by health workers were incomplete. The time required to document, health system challenges, status of mother at presentation, and the high workload undermined completion of the Partograph at this high volume facility.